Analysis of Plant Biomass Production Comparing Decoupled Aquaponics Against Equivalent Single-Loop Aquaponic and Hydroponic Systems Growing Lactuca Sativa - (:unkn) unknown (My University, 2020)
Aquaponics is an emerging method of agriculture in which fish and plants are grown in an enclosed and recirculating environment. The method mimics a relationship found in nature where fish waste provides nutrients for plants and plants cleanse the water for the benefit of the fish. This symbiotic relationship has proven to be a sustainable method of agriculture in which there is less water use, no need for pesticides or herbicides, recycling of nutrient waste and a smaller spatial footprint. However, the production of both plants and fish in a recirculating aquaponics system has produced less yield and profit when compared to its competitive counterparts, hydroponics and RAS (recirculating aquaculture system) methods. To address this issue, the traditional single recirculation aquaponics system (SRAPS) has been reengineered to a decoupled recirculation aquaponics system (DRAPS). The main differences of the DRAPS system is 1) solid waste from fish is mineralized and sent to the hydroponic plant grow system; 2) water from hydroponic system does not return to the fish; and 3) separate aquatic environments for fish and plants allow for the caretaker to create ideal growing conditions based on the specific needs of the culture organism. The objective of this study was to compare the yield of lettuce, Lactuca sativa, against three systems, hydroponics, SRAPS and DRAPS. The results of this study suggest that aquaponic environments provide a more habitable environment for plants to thrive over comparable hydroponic environments. Further research must be done to refine DRAPS and create a sustainable agriculture system to feed a growing world with less resources.
Keywords: aquaponics; hydroponics